Safety of wireless capsule endoscopy in patients with implantable cardiac devices. Issue 2 (4th September 2019) - Kasia, Christopher; Appannagari, Anoop; Joshi, Anjali; Venu, Mukund
Abstract : Background and Aim: Wireless capsule endoscopy (WCE) has become an increasingly utilized imaging modality for the evaluation of gastrointestinal bleeding. There is a paucity of data evaluating the safety and use of WCE in patients with implantable cardiac devices. Methods: A retrospective chart review of all patients who had a WCE at Loyola University Medical Center in Maywood, IL, USA completed between January 2007 and December 2016 identified patients with internal cardiac devices and obscure gastrointestinal bleeding. Patient WCE footage was viewed in its entirety before creating a final report to ensure no gaps in footage and video quality. Results: No patient complaints were documented during the 8‐h procedure duration, and there were no cardiac abnormalities noted on telemetry. There were no device‐related complications documented in the 30‐day postprocedure time period. Postprocedure analysis of the WCE recordings demonstrated no interference in WCE image quality (loss of images or gaps in video) or duration. Conclusions: There is no significant interference between WCE and implantable cardiac devices, and it appears to be safe to use. Abstract : Our study showed no adverse cardiac outcomes in patients with implantable cardiac devices receiving capsule endoscopy. Data quality from capsule endoscopy is not compromised in patients with implantable cardiac devices.